Generative Artificial Intelligence on the Scene of Higher Education in the Health Sciences - Magallan, Laura E.; Jalley, María V.; Giorgini, Gisele N.; Berk, Michelle D.; Kamerman, Mariana A.; Lacueva, Juan I.; Schwartzman, Gisela (Revista del Hospital Italiano de Buenos Aires, 2024)
Introduction: This article focuses on the experience of the Instituto Universitario Hospital Italiano de Buenos Aires in addressing artificial intelligence (AI) in education. The objective is to share lines of action and results to promote reflection and critical understanding of this technology within the educational community. Development: This article presents an experiential account related to the design of four lines of action to address the use of generative AI applications in higher education, specifically in the field of health sciences: the elaboration of a state of the art; an inquiry into the knowledge within the educational community; training for key institutional actors; and the production of guidance materials. Results: There is a growing interest in generative AI within the educational community. Positive experiences are documented with AI applications, finding them intuitive and valuable for research and teaching. However, challenges are also highlighted, such as the lack of knowledge on how to effectively use these tools. Training has been essential in addressing these challenges and has been provided to members of the Department of Education team, authorities, and educators. Conclusion: AI is fundamentally impacting higher education in the field of health sciences. Universities have a responsibility to promote the development of digital competencies and responsible usage criteria. As AI continues to evolve, it is crucial to address new challenges and regulations while promoting ongoing reflection and education within the academic community. Interdisciplinary collaboration and cooperation among various institutional management areas are essential to address these technological changes in education.